Adsorption of Sr(II) cations onto titanium dioxide, doped with Boron atoms - Mironyuk, Ivan; Vasylyeva, Hanna; Prokipchuk, Iryna; Mykytyn, Igor (Physics and Chemistry of Solid State, 2023)
The adsorption of Sr(II) cations by Boron-doped TiO2 was investigated. The adsorbent samples were obtained by liquid-phase sol-gel method using the aqua complex precursor [Ті(ОН2)6]3+‧3Cl- and modifying reagent hydrogen borate Н3ВО3. It was found, that single-phase rutile titanium dioxide or two-phase anatase-rutile oxide materials were formed under the different initial ratios of components. Boron atoms are combined with Oxygen atoms into triangular structural cell ВО3 in the rutile sample 0.5В-ТіО2 and are localized in the surface layer of the nanoparticle material as a grouping =О2ВОН. The introduction of Boron atoms into the structure of the rutile adsorbent causes an increase in its adsorption capacity for the binding of Sr(II) cations in the aqueous electrolyte. The maximal adsorption values for Sr(II) cations by the rutile adsorbent in a neutral electrolyte environment reach 102.3 mg‧g-1, while it is equal to 68.8 mg‧g-1 for the unmodified anatase adsorbent a-TiO2. The number of acid adsorption centers ≡ТіОНδ+ on the surface of the rutile adsorbent 0.5В-ТіО2 is 50 units on a surface area of 10 nm2, which is twice the number of centers on the surface of the anatase adsorbent a- ТіО2. Anatase-rutile adsorbents 1.0В-ТіО2 and 1.5В-ТіО2 contain, respectively, 70% and 57% of the anatase phase. They are significantly inferior in adsorption ability toward cations of Sr(II) compared with the rutile adsorbent 0.5В-ТіО2. This is because Boron atoms are mainly localized in the anatase phase and with oxygen atoms form tetrahedral groups of ВО4-.